Eyewitness Falklands : A Personal Account of the Falklands Campaign - Fox, Robert, 1945- (London Methuen, 1983)
An eye-witness account of the Falklands campaign
Include Illustration, Glossary and Index
Keywords: Fox, Robert, 1945 -- War correspondents -- Great Britain